A descriptive survey of entry-level placement of BS Clothing Technology graduates in relation to area of specialization - Umali, Janah Eloise P.
ABSTRACT The study determined the entry-level placement profile of BS Clothing Technology graduates in relation to the different areas of specialization in the garment industry. It described the characteristics, qualifications, duties and responsibilities of an entry-level position for a BS Clothing Technology graduate. Specifically, the study aimed to identify the areas of specialization where these job positions fall and to give details of job descriptions of these entry-level positions, particularly duties and responsibilities. The survey on entry-level placement of BS Clothing Technology graduates in relation to the areas of specialization is significant because it summarized an evaluation of critical fields in the garment industry such as merchandising and retail, production and quality control, fashion design, research and fashion journalism, and training and teaching. The research findings can help in the upgrading of the BS Clothing Technology Curriculum. The research design used was descriptive-survey approach and the sampling method applied was purposive sampling wherein criteria for choice was based on providing a current profile of the graduates and BS Clothing Technology graduates for the past three years were randomly selected. The respondents included twenty BS Clothing Technology graduates from school year 2005-2006 to 2008-2009. The instrument for data gathering was a survey questionnaire. Personal interviews were also conducted. The data collected were presented in descriptive form and categorized into five areas of specialization namely merchandising and retail, production and quality control, fashion design, research and fashion journalism, and training and teaching. Results showed that sixty percent of the respondents had entry level job placements in the area of merchandising and retail, twenty in fashion design, and ten percent in production and quality control. None of the respondents had entry level job placements in the fields of research and fashion journalism and training and teaching. The balance ten percent of the respondents had entry level job placements in areas outside the garment industry. It showed that merchandising was the most popular field that the BS Clothing Technology graduates pursue, followed by fashion design, then by production and quality control. The results explained that the BS Clothing Technology program should contemplate more on the areas of merchandising and design. The researcher recommends a larger sample size for further research in order to get a more accurate set of findings.